Foliar Application of Paclobutrazol at Different Dose in Avocado Seedlings (Persea americana Mill.) Cultivate Hass) Cultivar Hass - Navarro Brioso, Kevin Coquito (2020)
This researchworkwas carried out under nursery conditions inMajes, Arequipa; The objective was to determine the adequate dose of Paclobutrazol in avocado seedlings of the Hass cultivar, in which a completely randomized design (DCA) was used, with four treatments, three repetitions, with a total of 12 experimental units and the test was performed of Tukey’s mean comparison. The treatments were: Control 0 ppm (T0), 150 ppm (T1), 300 ppm (T2) and 450 ppm (T3) per 200 L respectively, applying a broth volume of 50 cc per plant; obtained the results, it was determined that the T3 presented a delay in the growth of the height of the shoots with an average of 23;67 cmand a shortening in the length of the internodes with an average of 1;73 cm; but the use of Paclobutrazol did not influence the diameter of the shoots.